Kewajiban Penggunaan Bahasa Indonesia dalam Perjanjian Sewa Komersial: Perspektif Yuridis dalam Hukum Kontrak Indonesia - Herlan, Asep; Rizqi, Aditya Maulana; Masturi, Frida Nurrahma; Iryatin, Al Fiani Nenden (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2025)
The difference of opinion among judges regarding the obligation to use Indonesian in rental agreements, as seen in District Court Decision Number 101/Pdt.G/2016/PN.Jkt.Sel and Supreme Court Decision Number 3230 K/Pdt/2018, creates legal uncertainty. This stems from confusion in interpreting whether the use of Indonesian is a halal causa requirement or merely a formality. This research employs a normative juridical method with statutory, conceptual, and case approaches. The findings indicate that halal causa relates to the substance of an agreement, not the language used. The South Jakarta District Court mistakenly viewed the obligation to use Indonesian as a halal causa requirement, while the Supreme Court misinterpreted it as a mere formality. In reality, the use of Indonesian is a formality condition, not a halal causa requirement. When drafting business agreements, parties must understand the validity conditions and legal requirements. To prevent inconsistencies, improving judicial decision-making quality is essential.